Ambulatory monitoring system for 24 hours of esophageal pH. - Hernández, H.; Morales, R.; Paulin, R. (Revista Mexicana de Ingenieria Biomedica, 2018)
A prototype based on the 8031 microcontroller is presented to detect the pH value in the distal esophagus and store the data in solid state memory, from where they are transferred to a computer. The advantages of the method are discussed and it is concluded that it is more convenient.